(untitled) (Tokyo, 1987)
Following the part one, this part 2 gives the tittles, author(s) names, and journal names of references in the order of the reference number.
Keywords: Plant tissue culture,Đời sống thực vật; Periodicals,Ấn phẩm định kỳ